The Aesthetical Relationship between Digital Music and History of Modernism - Santoso, Agus (TAWARIKH, 2015)
ABSTRACT: The used of the digital computer surely affects the born of postmodern aesthetic. This indication can be observed by looking at the music work that be produced. Every piece of it has aesthetical values, such as Pastiche, Kitsch, Parody, Camp, and Schizophrenic. These five values are the characteristics of aesthetical art produced by mass culture. This is an identity of postmodern culture. In mass culture, there is a sign of simulation system that does not reflect the signs out of itself, but it is a sign that represents the being of the sign itself. Moreover, behind the aesthetical value produced by the digital devices, it also creates the system of hyper-semiotics sign (beyond semiotic), because there are illusion signs like pseudo sign, false sign, and simulation sign. This writing is an analysis about the effect of modernity toward the value of digital musicâs aesthetic that be created by using computer devices. The purpose is to reveal how far is the effect of modernity toward the reproduction process of digital music, and also what does the beauty of a music work created by a computer look like. The basic assumption, as the background of this writing, is triggered by the awareness that the birth of digital music works cannot be separated from the development of the modern culture, such as computer device. By using computer, in the end, everyone can create music work easily, because the reproduction is so different with the one done by using manual ways. In doingÂ  this research, the writer uses historical approach, or diachronic, by looking at the present event, then connected to the previous time, so that the whole event can be identified.KEY WORDS: Effect of modernity, computer device, digital musicâs aesthetic, system of hyper-semiotics sign, historical approach, and postmodern culture.About the Author: Agus Santoso, M.Sn. is a Lecturer of Musical Art at the Faculty of Art and Literature Science UNPAS (Pasundan University), Jalan Dr. Setiabudhi No.193, Bandung, West Java, Indonesia. For academic interests, the author can be contacted via e-mail at: agus_bing@hotmail.comHow to cite this article? Santoso, Agus. (2015). âThe Aesthetical Relationship between Digital Music and History of Modernismâ in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.213-222. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (August 24, 2014); Revised (January 27, 2015); and Published (April 28, 2015).